AB1347 ASSESSMENT OF PATIENTS' KNOWLEDGE ABOUT BIOLOGIC THERAPY AS A SELF-COMPLETION QUESTIONNAIRE. IS IT A GOOD WAY TO DO IT?. (June 2019) - Madeira, Nathalie; Silva, Candida; Miguel, Claudia; Medeiros, Dina; Barcelos, Filipe; Santos, Helena; Trinca, Ricardo; Cardoso, Alexandra; Miranda, Luís Cunha
Abstract : Background: Lack of knowledge from a patient in his therapy may lead to a misuse process, increasing the probability of failure to achieve the therapeutic goal. Objectives: To evaluate if the assessment of the RA and SpA patients' knowledge in their biologic therapy could be done as a self-completion questionnaire. Methods: Observational cross-sectional study which included patients with RA according to 1987 ACR and/or 2010 ACR/EULAR criteria or SpA according to 2009 ASAS classification criteria (CC) for axial SpA or to 2011 ASAS CC for peripheral SpA (including patients with psoriatic arthritis), on subcutaneous biological therapy who agreed to participate. Patients' knowledge about their biologic therapy was assessed using the " Conhecimento do doente sobre os seus medicamentos " (CPM-PT-PT), meaning "Patient's knowledge about his medicines", intercultural adaptation for the Portuguese version of the original Spanish questionnaire, CPM-ES-ES. This questionnaire was created to be used as an interview, but we decided to give it to patients and ask them to complete it autonomously, reading the questions and writing their answers, considering only their biologic therapy. It consists of 11 questions, each with a score based on patient's answer: incorrect = -1, the patient doesn't know = 0, incomplete = 1 and correct = 2. The final score is calculated using the mathematical formula described by the authors, ranging from 0 (doesn't know the medicine) to 2 points (optimal knowledge). Statistics: descriptive, Mann-Whitney and Kruskal-Wallis tests and Spearman correlation, p <0.05. Results: We included 84 patients, 45 of which with SpA (53.6%) and 39 (46.4%) with RA. In the RA group, 92.3% were female, 84.6% were under anti-TNFα, 66.7% were under their 1st biologic, the median age was 60.0 (51.0-66.0) years and the median time in treatment with current biologic was 31.0 (20.0-62.0) months. In the SpA group, 62.2% were female, 86.7% were under anti-TNF, 77.8% were under their 1st biologic, median age was 47.0 (39.5-57.0) years and median time in treatment with current biologic was 37.0 (12.0-83.0) months. Fifteen incomplete questionnaires were excluded. Sixty patients (87.0% of the 69 valid questionnaires) didn't meet the minimum criteria necessary to ensure correct use of medication (correct answer to the first 5 questions), thus obtaining a CPM score of 0. The mean CPM score was 0.2±0.5, the median 0 (0), the minimum 0 and the maximum 1, 7. There were no differences in CPM according to age, time in treatment with the current biologic, disease duration, n° of previous biologics, gender, educational level, diagnosis, current biologic and n° of other concomitant drugs. Table 1 describes the scores obtained in each domain of the questionnaire. We noticed that if we ask the same questions orally, the patients knew more than what the questionnaire revealed. Conclusion: The CPM-PT-PT underestimated the level of knowledge about biologic therapy in our population, suggesting the need to assess it during the clinical interview. References: [1] Salmerón Rubio J, García Delgado P, Iglésias Ferreira P, Mateus Santos H, Martinez-Martinez F. Validación del cuestionario de medidada del conocimiento del paciente sobre su medicamento adaptado al português. Ciência & Saúde colectiva. 2014;19(4): 1141-50. Disclosure of Interests: Nathalie Madeira: None declared, Candida Silva: None declared, Claudia Miguel: None declared, Dina Medeiros: None declared, Filipe Barcelos Consultant for: Pfizer; Ely-Lilly, Speakers bureau: Novartis, Helena Santos: None declared, Ricardo Trinca: None declared, Alexandra Cardoso: None declared, Luís Cunha Miranda: None declared